Transitional Aid Research Project (TARP), 1976-1977 - Rossi, Peter ([Verlag nicht ermittelbar], 1984)
The Transitional Aid Research Project (TARP) was a randomized field experiment conducted in Texas and Georgia in 1976-1977 that was designed to reduce recidivism among ex-prisoners by lowering incentives for re-engaging in property crime through provision of minimal levels of income support and extension of some unemployment insurance coverage to released prisoners. This study evolved out of an earlier LIFE (Living Insurance for Ex-Prisoners) study conducted in Baltimore, Maryland in the early 1970s. In the LIFE study, 500 prisoners with a high probability of re-arrest were randomly assigned at release from prison to experimental and control groups which varied by the amount of money received (contingent upon employment or unemployment and job placement services provided). The results showed that ex-prisoners receiving payments were less likely to be re-arrested for property theft-related crimes than those who received only job placement or no services or payments of any kind. The United States Department of Labor commissioned the TARP experiment, designed to replicate the LIFE experiment while providing a larger and more representative sample of prisoners, greater variation in treatment conditions, and administration of payments and job placement services through existing agencies rather than by a special purpose project staff. Texas and Georgia were the states chosen for the experiment, and stratified random samples of inmates were assigned, at the time of release from prison, to experimental and control groups. The groups varied in the amount of money and job placement services they received upon their release. Originally, the data were recorded in nine files for each state corresponding to each of the nine different sources of information for each TARP case. The ICPSR data collection combines these into one file for each state: Part 1 for Texas, and Part 2 for Georgia. Each file contains over 1,500 variables, clustered in nine topic areas for each inmate: (1) prison history (e.g., background information, psychological and aptitude test data, and prior criminal and present incarceration activity), (2-5) data from four personal interviews (conducted at the prerelease, three-month, six-month, and 12-month stages and that include living arrangements, employment history, and financial status), (6) state arrest data, (7) records of TARP payments received, (8) social security wages, and (9) parole records.